How many species of cladocerans (Crustacea, Branchiopoda) are found in Brazilian Federal District? - Sousa,Francisco Diogo Rocha (2012)
AIM: This study aimed provides a checklist of cladocerans and also an evaluation of richness and species composition in the Federal District, Brazil. METHODS: Checklist of cladocerans was obtained evaluating data from the literature, from taxonomic collection (Elmoor-Loureiro's collection) and from fauna surveys conducted over more than three decades in different types of aquatic environments. RESULTS: The 57 water bodies studied showed 56 species, of which 14 are new records. The number of species contained in the list displayed corresponds to 85% of what was expected for richness estimators. The highest number of species was observed in the lentic water bodies (52), which also presented the specific composition of fauna (R = 0.110; p = 0.016), possibly because there were samples taken among the aquatic vegetation. According to our understanding, some species may be subject to local extinctions because they inhabit water bodies located exclusively in urban areas, which can lead to a decline in richness. CONCLUSION: Thus, the results of this study can assist in monitoring aquatic environments and in selection of new areas for surveys of cladocerans in the Federal District.